Fertility and organic matter compartments in soil under different management systems - Machado, Luciana Ventura; Rangel, Otacílio José Passos; Mendonça, Eduardo de Sá; Machado, Ramires Ventura; Ferrari, Jéferson Luiz (Coffee Science - ISSN 1984-3909, 2014)
The soil organic matter is influenced by management adopted, and for this reason, considered an indicator of soil quality and sustainability of agroecosystems. The objective of this study was to evaluate the changes in soil fertility and different organic matter compartments of an Oxisol under different management systems of a coffee plantation area under influence of the Atlantic Forest located in the district of Boa Esperança, Marechal Floriano in the state of Espírito Santo. Soil samples were collected at depths from 0-0,05 and 0,05-0,10m. The management systems samples were: NF (native forest), CC (intercropped coffee with fruits) and UC (unshaded coffee). Also, a physical and chemical analysis of the soil was done and quantified the contents of total organic carbon (TOC), total nitrogen (TN); carbon in different fractions also was quantified: humin (C-HUM), humic acids (C-HAF) and fulvic acids (C FAF). The values of C-HAF/C-FAF and C-HUM/(C-FAF+C-HAF), TOC stocks, TN stocks and the relation of TOC/TN in the soil were calculated. The replacement of native forest for cultivations of coffee changed the density and soil fertility. The coffee systems caused a reduction in content and stock of carbon and nitrogen in the soil. The forest showed equilibrium in the kinetics of decomposition of organic waste and release of N and other nutrients (P and K+) in the soil through litterfall. The deployment of agroecosystems caused changes in the behavior of humic substances, and intercropped coffee showed lowest organic cycling.